A series solution for free vibration of moderately thick cylindrical shell with general boundary conditions. (15th June 2018) - Zhang, Wei; Fang, Zheng; Yang, Xiao-Dong; Liang, Feng
Highlights: A novel series solution method is proposed to study cylindrical shell vibration, and the efficiency has been verified. The proposed method is suitable to treat general boundary conditions with elastic supports. The first-order shear deformation theory is considered to model the moderately thick cylindrical shell. Abstract: In this paper, a modified Fourier cosine series method for beams and plates is proposed for free vibration analysis of moderately thick cylindrical shell with general boundary conditions. Displacement functions are assumed as a superposition of Fourier cosine series and two types of supplementary functions. Traditional method for elastic constraint which has been used in the classical thin shells is extended to treat the moderately thick shell involving first-order shear theory. The advantage of the approach is that the method can conveniently solve general boundary conditions including elastic constraints in practical engineering field by only varying the stiffness coefficients.